The Mediation Role Of Job Satisfaction In The Relationship Between Leadership, Communication, Work Abilities On The Performance : Evidence From Bank Mandiri Employees At Rantauprapat Branch - Nurul Azmi (Garuda Prestasi Nusantara Consulting, 2023)
The purpose of this research is to determine the mediating role of job satisfaction in the relationship between leadership, communication, work ability and employee performance at Bank Mandiri Rantauprapat Branch. The research method uses multiple linear regression analysis which is processed using SmartPLS3. The research results prove that the variable job satisfaction can mediate the influence of leadership, communication and work ability on employee performance. Obtaining the results of hypothesis testing directly using bootstrapping variables of leadership, communication, work ability has a positive and significant effect on employee performance.